Serum cortisol concentrations in newborn foals are increased by transfusion with anti-rhodococcal hyperimmune plasma and inversely associated with immunoglobulin activity - Kira C. Sayre; Patricia Flores-Ahlschwede; Alexandra B. Wethington; Susanne K. Kahn; Jocelyne M. Bray; Devynn M. Volding; Scott Ahlschwede; Angela I. Bordin; Noah D. Cohen; Thomas H. Welsh (Journal of Equine Veterinary Science, 2026)

Teaching Kitchen Experience in a Pediatric Weight Management Clinic to Increase Nutrition Knowledge and Confidence - W. Palmer; B. McIntire; M. Routly-Mansfield; J. Welsh; K. Shary; A. Van Cise (Journal of the Academy of Nutrition and Dietetics, 2025)

Telehealth Counseling by a Registered Dietitian to Increase Access to Pediatric Obesity Care - W. Palmer; C. Waddle; M. Routly-Mansfield; B. McIntire; J. Welsh (Journal of the Academy of Nutrition and Dietetics, 2025)

Monitoring population-level foraging distribution of a marine migratory species from land: strengths and weaknesses of the isotopic approach on the Northwest Atlantic loggerhead turtle aggregation - Simona A. Ceriani; Susan Murasko; David S. Addison; David Anderson; Greg Curry; Nicole A. Desjardin; Scott F. Eastman; Daniel R. Evans; Nancy Evou; Mariana M. P. B. Fuentes; Matthew H. Godfrey; Kristen M. Hart; et al. (Frontiers in Marine Science, 2023)
Assessing the linkage between breeding and non-breeding areas has important implications for understanding the fundamental biology of and conserving animal species. This is a challenging task for marine species, and in sea turtles a combination of stable isotope analysis (SIA) and satellite telemetry has been increasingly used. The Northwest Atlantic (NWA) loggerhead ( Caretta caretta ) Regional Management Unit, one of the largest sea turtle populations in the world, provides an excellent opportunity to investigate key biological patterns as well as methodological aspects related to the use of stable isotopes to infer spatial distribution of turtles in foraging areas. We provide the first comprehensive assessment of the annual distribution of NWA adult female loggerheads among foraging areas and investigate the efficacy of various analytical approaches as well as the effect of sample size in these types of studies. A total of 5168 individual females were sampled from seven Management Units (MUs) between 2013-2018. We provide the first estimate of the proportion of females originating from each MU that uses each foraging area and show how this proportion varies over time. We also estimate the relative importance (in terms of number of turtles) of each foraging area to the overall loggerhead breeding aggregation nesting in Florida and in the NWA for each year of the study. The foraging area used by reproductively active females differs considerably across MUs. One of these, the Subtropical NWA, is by far the most important foraging area in terms of both number of individuals and genetic diversity, and therefore this region may be considered as a conservation priority. Through simulations, we show that limited sizes of sample groups (unknowns; training; priors) may result in false geographic differentiation and consequently mislead interpretations. We provide thresholds and methodological recommendations for future studies. This study establishes a fundamental baseline for monitoring the annual contribution of foraging area to a terrestrial-based breeding aggregation of a marine animal in a cost-effective way. This type of monitoring allows for early detection of changes in foraging distributions—a possible effect of climate change on marine ecosystems or of area-specific anthropogenic threats.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Insights from a novel, user-driven science transfer program for resource management - J. L. M. Hinderer; Z. Blevins; S. J. Cooke; E. Dunlop; K. F. Robinson; D. L. Stang; T. J. Stewart; J. T. Tyson; A. B. Welsh; N. Young; A. M. Muir (Socio-Ecological Practice Research, 2021)
Research results are often not easily accessible or readily digestible for decision-making by natural resource managers. This knowledge-action gap is due to various factors including the time lag between new knowledge generation and its transfer, lack of formal management structures, and institutional inertia to its uptake. Herein, we reflect on the Great Lakes Fishery Commission’s Science Transfer Program and its evolution from ‘Mode 1’ (i.e., scientists conduct research autonomously) toward ‘Mode 2’ (i.e., co-production of knowledge with practitioners) knowledge production to understand and overcome the knowledge-action gap. Six success factors and strategies and tactics used to achieve those factors were critical to the shift from Mode 1 to Mode 2: (1) dedicate funding and staff support; (2) obtain top-down commitment from organizational leadership; (3) break down silos; (4) build relationships through formal and informal interactions; (5) emphasize co-production in program and project implementation; and (6) obtain buy-in among relevant actors. By way of three project case studies, we highlight knowledge transfer approaches, products, and lessons learned. We anticipate this contribution will benefit those working on knowledge mobilization, particularly in boundary-spanning organizations, and those involved in resource program management, administration, and design; it is also intended for resource managers seeking to have their science and information needs met more effectively.

Genetic swamping and possible species collapse: tracking introgression between the native Candy Darter and introduced Variegate Darter - Isaac Gibson; Amy B. Welsh; Stuart A. Welsh; Daniel A. Cincotta (Conservation Genetics, 2019)

Variation in DNA methylation is associated with migratory phenotypes of lake sturgeon Acipenser fulvescens in the St. Clair River, MI, USA - Justine M. Whitaker; Amy B. Welsh; Darryl W. Hondorp; James C. Boase; George T. Merovich; Stuart Welsh; Charles Krueger (Journal of Fish Biology, 2018)
Lake sturgeon Acipenser fulvescens populations show a variety of movement patterns that are poorly understood. To compare two migratory phenotypes of A. fulvescens in the St. Clair River, MI, USA, multiple data types were analysed. Individual fish were classified into migratory phenotypes based on acoustic telemetry data collected 2012–2015. Acipenser fulvescens consistently showed movement from the St. Clair River upriver into Lake Huron or downriver into Lake St. Clair. The two migratory phenotypes were then compared for differences in morphometrics, genetics and epigenetics. Morphological differences based on linear measurements were not detected between phenotypes. Microsatellite data from 11 loci suggested one population with no genetic differentiation between migratory phenotypes. Our epigenetic results indicated that the migratory phenotypes are differentially methylated ( P A. fulvescens . Only one restriction site was identified to be driving the differential methylation ( P A. fulvescens , DNA methylation may play a role in the observed movement pattern variation. When combined with microsatellite and morphometric analyses, our results suggested that different migratory patterns may reflect phenotypic plasticity, allowing A. fulvescens to acclimate to short‐term environmental variability. Without an integrated approach, the role of epigenetics in the migratory phenotype of A. fulvescens may have been overlooked. Further characterization of migratory phenotypes could be important for management to conserve behavioural variation across the distribution of A. fulvescens and for design of stocking guidelines.

The effect of multiple spawning events on cohort genetic diversity of lake sturgeon (Acipenser fulvescens) in the Kaministiquia River - Amy B. Welsh; Melinda R. Baerwald; Michael Friday; Bernie May (Environmental Biology of Fishes, 2015)

Response of benthic macroinvertebrate communities to highway construction in an Appalachian watershed - Lara B. Hedrick; Stuart A. Welsh; James T. Anderson; Lian-Shin Lin; Yushun Chen; Xinchao Wei (Hydrobiologia, 2010)

Relationship Between the Endophyte Embellisia spp. and the Toxic Alkaloid Swainsonine in Major Locoweed Species (Astragalus and Oxytropis) - M. H. Ralphs; R. Creamer; D. Baucom; D. R. Gardner; S. L. Welsh; J. D. Graham; C. Hart; D. Cook; B. L. Stegelmeier (Journal of Chemical Ecology, 2008)

Use of tag data to compare growth rates of Atlantic coast striped bass stocks - S. A. Welsh; A. W. Kahnle; B. A. Versak; R. J. Latour (Fisheries Management and Ecology, 2003)
Migratory stocks of Atlantic coast striped bass, Morone saxatilis (Walbaum), range primarily from North Carolina (NC) northward to Canadian waters. Between 1986 and 2000, 267 045 wild striped bass were tagged and released from NC to Massachusetts as part of the Cooperative Striped Bass Tagging Program. Direct measurements of growth of individual fish can be obtained from tag data and are useful for understanding the dynamics of fish populations. Growth rates from regressions of length‐increment vs. time‐at‐liberty were estimated for striped bass tagged and released in three southern states [NC, Virginia (VA) and Maryland (MD)] and three northern states (New Jersey, New York and Rhode Island). Striped bass tagged in waters of northern states grew faster (significantly steeper regression slopes) than those tagged in southern areas. Migratory patterns, stock mixing, and unmeasured biotic and abiotic influences on growth precluded conclusions that observed growth patterns are stock‐specific. These results, however, indicate latitudinal differences in growth rates, and should be considered in future research and management of Atlantic coast striped bass.

A non-aphid-transmissible isolate of bean yellow mosaic potyvirus has an altered NAG motif in its coat protein - S. J. Wylie; J. Kueh; B. Welsh; L. J. Smith; M. G. K. Jones; R. A. C. Jones (Archives of Virology, 2002)

Sulphate reduction and nitrogen fixation rates associated with roots, rhizomes and sediments from Zostera noltii and Spartina maritima meadows - Lise B. Nielsen; Kai Finster; David T. Welsh; Andrew Donelly; Rodney A. Herbert; Rutger De Wit; Bente AA. Lomstein (Environmental Microbiology, 2001)
Sulphate reduction rates (SRR) and nitrogen fixation rates (NFR) associated with isolated roots, rhizomes and sediment from the rhizosphere of the marine macrophytes Zostera noltii and Spartina maritima , and the presence and distribution of Bacteria on the roots and rhizomes, were investigated. Between 1‰ and 3‰ of the surface area of the roots and rhizomes of both macrophytes were colonized by Bacteria. Bacteria on the surfaces of S. maritima roots and rhizomes were evenly distributed, while the distribution of Bacteria on Z. noltii roots and rhizomes was patchy. Root‐ and rhizome‐associated SRR and NFR were always higher than rates in the bulk sediment. In particular, nitrogen fixation associated with the roots and rhizomes was 41–650‐fold higher than in the bulk sediment. Despite the fact that sulphate reduction was elevated on roots and rhizomes compared with bulk sediment, the contribution of plant‐associated sulphate reduction to overall sulphate reduction was small (≤ 11%). In contrast, nitrogen fixation associated with the roots and rhizomes accounted for 31% and 91% of the nitrogen fixed in the rhizosphere of Z. noltii and S. maritima respectively. In addition, plant‐associated nitrogen fixation could supply 37–1613% of the nitrogen needed by the sulphate‐reducing community. Sucrose stimulated nitrogen fixation and sulphate reduction significantly in the root and rhizome compartments of both macrophytes, but not in the bulk sediment.

Characteristics of a cetacean morbillivirus isolated from a porpoise (Phocoena phocoena) - M. J. Welsh; C. Lyons; A. Trudgett; B. K. Rima; S. J. McCullough; C. rvell (Archives of Virology, 1992)